Pre-COVID-19 epidemiology of community respiratory viruses at a single US center reveals sex differences in influenza A and a higher ICU incidence of human metapneumovirus in the elderly population - Bibek Koirala; Aline Azar; Brianna Fountain; Melissa McGuirl; Shannon Stock; Marzena Galdzicka; Richard T. Ellison (BMC Infectious Diseases)
Abstract Background Few studies have simultaneously examined the epidemiology and sex differences of diverse community respiratory viruses, including human metapneumovirus (HMPV), over more than one season. Methods Given that molecular testing for community respiratory viruses was widely performed on patients at UMass Memorial Medical Center between January 2010 and December 2013, a retrospective study was conducted to examine epidemiologic features of positive subjects. Initial testing was done with rapid influenza and respiratory syncytial (RSV) virus antigen testing, with negative testing reflexed to a multiplex nucleic acid amplification platform detecting nine respiratory viruses. Results Four thousand ninety-eight (50.6%) of 8092 patients tested positive for at least one virus. The majority (75.3%) of individuals testing positive were inpatients. Rhinovirus/enterovirus was most frequently detected; influenza A was more common in older adults and RSV incidence was highest among patients < 5 years of age. Pronounced seasonality was seen with influenza viruses, RSV, HMPV, and parainfluenza 3 virus. Influenza A was significantly more common in females (11.2% vs. 8.1%; p < 0.001), while parainfluenza 1 virus (2.0% vs. 1.2%; p < 0.01), rhinovirus/enterovirus (23.4% vs. 19.9%; p < 0.001) and adenovirus (2.1% vs. 1.5%; p < 0.05) were significantly higher in males. Of the ICU patients with HMPV, many (40.3%) were ≥ 65 years of age. Conclusions This pre-coronavirus disease 2019 (COVID-19) era study has one of the largest patient populations evaluated for community respiratory virus infections. It confirms known epidemiology, seasonality, and coinfections, and importantly shows a preponderance of influenza A infections among women, contrasting prior studies, which warrants further investigation. It also shows a high HMPV incidence in the ICU among the elderly, underscoring the importance of testing in this population.